Temperature- and acceptor-specificity of cell-free vesicular transfer from transitional endoplasmic reticulum to the cis Golgi apparatus. - Dunkle, S (1992)
The temperature dependence and specificity of transfer of membrane constituents from donor transitional endoplasmic reticulum to the cis Golgi apparatus were investigated using a cell-free system from rat liver. The radiolabelled transitional endoplasmic reticulum donors were prepared from slices of rat liver prelabelled with [14C]leucine. The acceptor Golgi apparatus elements were unlabelled and immobilized on nitrocellulose. When Golgi apparatus stacks were separated by preparative free-flow electrophoresis into subfractions enriched in cisternae derived from the cis, medial and trans portions of the stack respectively, efficient specific transfer was observed only to cis elements. Trans elements were devoid of specific acceptor capacity. Similarly, when transfer was determined as a function of temperature, a transition was observed in transfer activity between 12 degrees C and 18 degrees C similar to that seen in vivo for formation of the so-called 16 degrees C cis Golgi-located membrane compartment. Transfer at temperatures below 16 degrees C and transfer to trans Golgi apparatus compartments at temperatures either above or below 16 degrees C was similar and unspecific. The unspecific transfer at low temperature was pH independent, whereas specific transfer was greatest at the physiological pH of 7, and was reduced to 10% and 18% of that occurring at pH 8 and pH 5.5 respectively. These findings show that the cell-free system derived from rat liver exhibits a high degree of fidelity to transfer in vivo, an efficiency approaching that observed in vivo, and a nearly absolute acceptor specificity for cis Golgi apparatus. The acceptor-, temperature- and pH-specificity of the cell-free transfer, as well as the saturation kinetics exhibited with respect to acceptor Golgi apparatus, support the concept of transition-vesicle-specific docking sites of finite number associated with cis Golgi apparatus cisternae.